A review on integrated approaches for municipal solid waste for environmental and economical relevance: Monitoring tools, technologies, and strategic innovations. (December 2021) - Kundariya, Nidhi; Mohanty, Swayansu Sabyasachi; Varjani, Sunita; Hao Ngo, Huu; W. C. Wong, Jonathan; Taherzadeh, Mohammad J.; Chang, Jo-Shu; Yong Ng, How; Kim, Sang-Hyoun; Bui, Xuan-Thanh
Graphical abstract: Highlights: Waste monitoring using high-end technologies has been discussed. Integration of technological approaches is needed for efficient waste management. Compiled environmental and economical relevance of waste management technologies. Strategic innovations in municipal solid waste management have been focused. Tools for hazard monitoring have been included. Abstract: Rapid population growth, combined with increased industrialization, has exacerbated the issue of solid waste management. Poor management of municipal solid waste (MSW) not only has detrimental environmental consequences but also puts public health at risk and introduces several other socioeconomic problems. Many developing countries are grappling with the problem of safe disposing of large amounts of produced municipal solid waste. Unmanaged municipal solid waste pollutes the environment, so its use as a potential renewable energy source would aid in meeting both increased energy needs and waste management. This review investigates emerging strategies and monitoring tools for municipal solid waste management. Waste monitoring using high-end technologies and energy recovery from MSW has been discussed. It comprehensively covers environmental and economic relevance of waste management technologies based on innovations achieved through the integration of approaches.